The Role of Room Attendants and Room Cleaning Standard Operating Procedures (SOPs) in Improving Employee Performance in the Housekeeping Department - Robinta Samura; Dina Octavia (CV. Muris Global Education, 2026)
This study focuses on the role of room attendants and room cleaning standard operating procedures in improving the performance of housekeeping department employees at the Sibayak International Hotel in Baerastagi, Karo Regency. The research method used was qualitative, using observation and interviews. Interviews were conducted with supervisors and room attendants. The results indicate that room attendants play a crucial role in maintaining room cleanliness, guest comfort, and satisfaction at the hotel. However, several obstacles remain in the implementation of standard operating procedures in the field. High occupancy rates increase the number of rooms to be cleaned, resulting in limited working time and operational equipment. This results in the ineffectiveness of SOPs. This study provides recommendations for improving compliance with standard operating procedures to ensure optimal guest cleaning services. Implementing standard operating procedures can improve room attendant performance.